PELATIHAN PENYUSUNAN LAPORAN KEUANGAN BERBASIS EXCEL PADA LPD DESA ADAT KUUM KELADI TABANAN - Nurcahya, I.N.; Sulistyawati, E.; Jember, I.M.; Wirawati, N.G.P. (Buletin Udayana Mengabdi, 2018)
Lembaga Perkreditan Desa (LPD) is one of the institution that is now a footstool for the people in order to fulfill their daily needs and fund management. This institution is formed to be able to have a bigger role in order to overcome the financial difficulties between the people. With that bigger and important role, LPD’s development become really fast. The Training of Arranging the Financial Report Based on Microsoft Excel that had been held in LPD Kuum Kladi Village Office aims to give knowledge to the LPD’s staff about the importance of being quick and accurate on making financial report. The training in LPD Office, which is in Banjar Adat Munduk Juwet were attended by all of the LPD staffs and 2 Bendesa Adat. This training went well and received a good welcome and enthusiasm from the community leader nor LPD staffs.